1998
DOI: 10.1038/sj.onc.1202002
|View full text |Cite
|
Sign up to set email alerts
|

The activation and composition of FiRE (an FGF-inducible response element) differ in a cell type- and growth factor-specific manner

Abstract: The expression of the heparan sulfate proteoglycan, syndecan-1, is induced both in keratinocytes and in ®broblasts during development and tissue regeneration. Here we report that in keratinocytes the syndecan-1 gene was stimulated by EGF but not by FGF-2. In ®broblasts it was stimulated by FGF-2 but not by EGF. Likewise, the recently discovered FGF-inducible response element (FiRE) on the gene of syndecan-1 was stimulated by FGF-2 in ®broblasts and by EGF in keratinocytes, but not vice versa. The FiRE has two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…The most 3Ј-motif (motif 1) of the enhancer binds an uncharacterized 46-kDa protein constitutively expressed in 3T3 cells (21). The DNA binding activity of this protein was equally present in treated and control MCA-3D cells and was unchanged by extracellular matrix molecules (data not shown).…”
Section: Kgf Fails To Activate Fire In Cells Plated On Fibrillarmentioning
confidence: 94%
See 4 more Smart Citations
“…The most 3Ј-motif (motif 1) of the enhancer binds an uncharacterized 46-kDa protein constitutively expressed in 3T3 cells (21). The DNA binding activity of this protein was equally present in treated and control MCA-3D cells and was unchanged by extracellular matrix molecules (data not shown).…”
Section: Kgf Fails To Activate Fire In Cells Plated On Fibrillarmentioning
confidence: 94%
“…Finally, we have found that an enhancer for syndecan-1 gene (named FiRE for FGF-inducible response element) is activated in vivo in wound edge keratinocytes and that in cultured keratinocytes, FiRE can be activated by KGF and EGF (21,22). Interestingly, this enhancer element is not sufficient for the default expression in suprabasal cells: the only epidermal expression detected in the FiRE-LacZ mice occurs at the wound edge (22).…”
mentioning
confidence: 98%
See 3 more Smart Citations